2011
DOI: 10.1007/s13361-011-0170-4
|View full text |Cite
|
Sign up to set email alerts
|

Tandem MS Analysis of Selenamide-Derivatized Peptide Ions

Abstract: Our previous study showed that selenamide reagents such as ebselen and N-(phenylseleno) phthalimide (NPSP) can be used for selective and rapid derivatization of protein/peptide thiols in high conversion yield. This paper reports the systematic investigation of MS/MS dissociation behaviors of selenamide-derivatized peptide ions upon collision induced dissociation (CID) and electron transfer dissociation (ETD). In the positive ion mode, derivatized peptide ions exhibit tag-dependent CID dissociation pathways. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…It was previously reported that NPSP-derivatized peptides undergo Se-S cleavage upon ETD or CID [28]. Thus, for comparative purposes, collision-based (CID and HCD) and ETD promoted cleavage of up to two S-Se cleavages in conjunction with charge reduction for tagged aprotinin; the analogous MS/MS spectra for cytochrome c were not readily interpretable.…”
Section: Other Activation Methods (Hcd Etd Cid)mentioning
confidence: 94%
See 1 more Smart Citation
“…It was previously reported that NPSP-derivatized peptides undergo Se-S cleavage upon ETD or CID [28]. Thus, for comparative purposes, collision-based (CID and HCD) and ETD promoted cleavage of up to two S-Se cleavages in conjunction with charge reduction for tagged aprotinin; the analogous MS/MS spectra for cytochrome c were not readily interpretable.…”
Section: Other Activation Methods (Hcd Etd Cid)mentioning
confidence: 94%
“…Fast, efficient, and selective selenylation of cysteine-containing species has been achieved previously using NPSP (Scheme 1) [27][28][29]. Additionally, online electrolytic cleavage of disulfides via an electrochemical cell prior to reactions with NPSP and mass spectrometry analysis has been reported as a means to identify disulfide-containing peptides in digests [30].…”
Section: Introductionmentioning
confidence: 99%
“…NPSP has been shown previously to yield fast and efficient derivatization of free cysteine residues. [52][53][54][55] Other methods for detecting cysteine-containing residues based on mass shifts due to the loss of different hydroquinone derivatives have also been explored and shown to …”
Section: Introductionmentioning
confidence: 99%
“…Several groups have begun to explore the derivatization of peptides with tags containing selectively cleavable groups in order to promote bond-selective cleavages [29][30][31][32][33][34][35][36]. Part of this strategy is derived from the concept that low energy collisional activation favors cleavage of the most labile bonds, thus motivating interest in installing bonds with low dissociation energies to enhance site-specific cleavages.…”
Section: Introductionmentioning
confidence: 99%
“…Typical energies of CÀ ÀC and CÀ ÀO bonds fall in the range of 350-360 kJ/mol [37], whereas others are much lower: an SÀ ÀS bond energy is around 305 kJ/mol, a CÀ ÀS bond energy is around 270 kJ/mol, and an NÀ ÀN bond falls in the range of 165 kJ/mol, less than half of the energy of CÀ ÀC and CÀ ÀO bonds [37]. One group reported the cleavage of SeÀ ÀS bonds in protonated peptides upon CID or ETD, in which the unusual SeÀ ÀS bond was installed via the derivatization of cysteine-containing peptides with an appropriate seleniumcontaining reagent [36]. Other groups have incorporated tags, such as TEMPO [34], Vazo 68 [33], or N-terminal lysine side chain derivatization to t-butyl peroxycarbamate, that generate radical ions upon CID [29].…”
Section: Introductionmentioning
confidence: 99%